BAHAN AJAR PROYEK PENGUATAN PROFIL PELAJAR PANCASILA DALAM MENINGKATKAN KEMANDIRIAN DAN KREATIVITAS SISWA SEKOLAH DASAR: A SYSTEMATIC LITERATURE REVIEW - Farida, Aida; Akbar, Wawan; Damanik, Sanra Hanalide; Hasratuddin (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2024)
Teaching materials play a crucial role in facilitating and enhancing the creativity and independence of elementary school students. P5 teaching materials refer to learning materials designed to support the Project-Based Learning (PBL) approach. This approach prioritizes project-based learning where students are directly involved in projects that require them to complete complex tasks and connect to real-world problems. This research is a systematic review research with the aim of determining the effectiveness of P5 teaching materials in increasing the independence and creativity of elementary school students. Searches for journal articles were carried out through the Publish or Perish application found in the Google Scholar electronic database with the keyword project to strengthen the profile of Pancasila students. The initial search found 322 journal articles, after being reviewed by inclusion, 7 journal articles were found to be reviewed systematically. The results of the systematic review found that from several articles reviewed it was found that the development of P5 teaching materials, especially in increasing student creativity and independence, had not yet been worked on much by researchers. It becomes something important if this is used as a study to provide more insight and new views in developing comprehensive teaching materials in overseeing every student learning activity